Research on smart cargo handling equipment in the next generation container ports - Chow, Venessa Qi Hui (2017)
Issues such as global warming and productivity are two major concern in today’s society. Especially true for productivity due to labour shortage in Singapore context. Given that population growth continues to increase over the years, this will have an impact on shipping activities. Much literatures review have researched on topic such as routing and scheduling of container handling equipment to improve productivity. However, nothing much has been done on exploring innovation of forklifts with respect to the cost, power consumption and emission reduction rate in order to enhance productivity as well as to achieve sustainable practices.